Seasonal variation in trophic structure and community niche dynamics of an Arctic coastal community of marine vertebrates - Matthew Fuirst; Kyle H. Elliott; Steven H. Ferguson; Aaron T. Fisk; Les N. Harris; Kevin J. Hedges; Kevin B. Jacobs; Kelsey F. Johnson; Tracey N. Loewen; Cory J. D. Matthews; C.J. Mundy; Andrea Niemi; et al. (Arctic Science, 2024)
Temporal variation in food web structure is widespread among highly seasonal environments, such as the Arctic, and is driven by changes in resource availability. Variation in resource availability can lead to species differences in diet composition, isotopic niche width, and trophic position (TP) across seasons. Here, we used tissue samples that represent two distinct turnover rates for diet (liver = shorter term, muscle = longer term) from 18 fish and three marine mammal species to investigate seasonal (i) variation in TPs within the Southampton Island marine ecosystem of Hudson Bay, (ii) variation in consumer isotopic niche width within this part of the food web, and (iii) variation in community niche dynamics among a fish and marine mammal community using stable carbon (δ13C) and nitrogen (δ15N) isotope analyses. Many zooplanktivores and piscivores increased in TP in summer (i.e., shorter-term turnover period), whereas benthic feeders dependent on ice-obligate prey decreased in TP. Most isotopic niche widths and community metrics (δ15N range, total ellipse area, mean centroid distance) were higher in liver than muscle. Our findings demonstrate seasonal changes in TPs, which suggests that Arctic communities may be differentially affected by longer ice-free periods and earlier onset of primary production due to accelerated climate change.